Editorial - Judith Winters (Internet Archaeology, 2002)
I come from a family who likes looking for patterns in numbers and things in general, and it certainly came as no surprise that my sister got married earlier this year on 20-02-2002! So I sat down at my desk to write this editorial and saw a pleasing even spread of articles and reviews that make up this journal issue. The number 4 is obviously my number of the week because I have been working on Internet Archaeology for 4 years this month - since May 4th 1998 to be exact!